2018
DOI: 10.1007/s00709-018-1307-0
|View full text |Cite|
|
Sign up to set email alerts
|

Ultrastructure and secretion of glandular trichomes in species of subtribe Cajaninae Benth (Leguminosae, Phaseoleae)

Abstract: The subtribe Cajaninae of papilionoid legumes has a pantropical distribution and comprises approximately 490 species. These species have diversified throughout dry environments where there are high temperatures and strong light. The subtribe stands out because all its representatives have vesicular glands. In addition, bulbous-based and capitate trichomes are important secretory structures present in all genera of the Cajaninae. We analyzed the ultrastructure and histochemistry of these glandular trichome type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…In agreement with our observations Oosthuizen and Coetzee (1983), confirm that accumulation and release of secretion are repeatable due to the development of a new cuticle beneath the ruptured layer. Similar accumulation of secretion in the subcuticular space and its release through a cuticle perforation has been reported in other representatives of the subfamily Faboideae (Zarinkamar and Sharebian 2016;Vargas et al 2019) and in the subfamily Caesalpinioideae (Paiva and Machado 2006;Souza et al 2013).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…In agreement with our observations Oosthuizen and Coetzee (1983), confirm that accumulation and release of secretion are repeatable due to the development of a new cuticle beneath the ruptured layer. Similar accumulation of secretion in the subcuticular space and its release through a cuticle perforation has been reported in other representatives of the subfamily Faboideae (Zarinkamar and Sharebian 2016;Vargas et al 2019) and in the subfamily Caesalpinioideae (Paiva and Machado 2006;Souza et al 2013).…”
Section: Discussionsupporting
confidence: 79%
“…Globose trichomes are present in representatives of the tribe Desmodieae (Freitas et al 2014). Spherical and ellipsoid trichomes (Flores et al 2019) and bulbous-based trichomes (Seixas et al 2019;Vargas et al 2019) have been described in plants from the tribe Phaseoleae, and cavitated secretory trichomes have been detected in members of the tribe Indigofereae (Marquiafável et al 2009;Pignal and De Queiroz 2019). As suggested by these authors, the morphologically diverse trichomes in the different plant taxa in the subfamily Faboideae are important taxonomic traits useful for identification and classification of different taxa at the level of species, genus, subtribe, or tribe and for investigations of phylogenetic relationships.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Excretion from a periplasmic space of the upper cell layers pass through the cell wall, accumulate in the subcuticular cavity, and rupture it (Muravnik et al 2019). Depending on the function, each morphotype of these glands is characterised by varied responses in the defence of plants against environmental factors (Tozin et al 2017;De Vargas et al 2019). It has been found that the characteristics of trichomes and stomata are associated with immunity of mulberry to powdery mildew and can be indicators of this type of immunity in cultivation programs (Chattopadhyay et al 2011).…”
Section: Micromorphologymentioning
confidence: 99%